Association study of the calcitonin gene-related polypeptide-alpha (CALCA) and the receptor activity modifying 1 (RAMP1) genes with migraine - Sutherland, H.G.; Buteri, J.; Menon, S.; Haupt, L.M.; MacGregor, E.A.; Lea, R.A.; Griffiths, L.R. (Gene, 2013)
Migraine is a common neurovascular brain disorder characterised by recurrent attacks of severe headache that may be accompanied by various neurological symptoms. Migraine is thought to result from activation of the trigeminovascular system followed by vasodilation of pain-producing intracranial blood vessels and activation of second-order sensory neurons in the trigeminal nucleus caudalis. Calcitonin gene-related peptide (CGRP) is a mediator of neurogenic inflammation and the most powerful vasodilating neuropeptide, and has been implicated in migraine pathophysiology. Consequently, genes involved in CGRP synthesis or CGRP receptor genes may play a role in migraine and/or increase susceptibility. This study investigates whether variants in the gene that encodes CGRP, calcitonin-related polypeptide alpha (CALCA) or in the gene that encodes a component of its receptor, receptor activity modifying protein 1 (RAMP1), are associated with migraine pathogenesis and susceptibility. The single nucleotide polymorphisms (SNPs) rs3781719 and rs145837941 in the CALCA gene, and rs3754701 and rs7590387 at the RAMP1 locus, were analysed in an Australian Caucasian population of migraineurs and matched controls. Although we find no significant association of any of the SNPs tested with migraine overall, we detected a nominally significant association (p=0.031) of the RAMP1 rs3754701 variant in male migraine subjects, although this is non-significant after Bonferroni correction for multiple testing. ► Calcitonin gene-related peptide (CGRP) is involved in migraine pathophysiology. ► We studied SNPs in the genes for CGRP and its receptor for association with migraine. ► The RAMP1 rs3754701 A-allele showed an association with migraine in male subjects.